Analisis Hukum Perkawinan Adat Masyarakat Desa Pulau Buaya Alor dalam Sistem Kekerabatan Adat ditinjau dari Perspektif Hukum Islam - Muhammad Fidlilal Ihsan Rakhmat; Muhamad Farudin; Suryo Damar Priluckito Hanjayanto; Ainul Fazhilla; Aulia Darusman; Alzahra Munawaroh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Traditional marriage in Pulau Buaya Village is not just the union of two individuals, but also a bond between two large families that involves social, cultural, and economic aspects. The traditional marriage customs in this village have significant stages that reflect the values of collectivism and respect for ancestors. However, the majority of the community also adheres to Islam, which has its own legal rules regarding marriage. The interaction between customary law and Islamic law in marriage practices often results in adaptations or acculturation that do not always proceed smoothly. Some traditional customs sometimes conflict with the principles of Islamic law, creating challenges in balancing the preservation of traditions with adherence to religious teachings. This study uses a juridical-empirical method with a qualitative approach. Primary data is obtained through interviews and direct observation of traditional leaders, religious leaders, and couples who have undergone traditional marriages. Secondary data is gathered from literature studies on customary law and Islamic law. The findings show that the customary marriage law in Pulau Buaya Village has been adjusted to Islamic principles, but practices still exist that contradict Islamic law. The implications of this study are the need for an integrative approach in formulating marriage policies that respect cultural diversity while remaining in accordance with Islamic and national legal principles.